(untitled) - ARIF R., ANGGIATAMA (LATERNE, 2016)
PReP Technique is applied as an alternative method of Reading comprehension to German language. This Method allows students whom can understand the passage clearly and gain the main of a passage. PReP Technique helps students more active and improve cognitive students to present information from Reading Text. The Research is conducted in SMA Negeri 12 Surabaya. The Background of Research is importance of Mental Activation Processes in the Cognitive system, and memory optimization of students in order to show their own abilities. The purpose of this research is to apply the PReP Technique on Reading comprehension in XI IPA 2 SMA Negeri 12 Surabaya in Alltagsleben theme. In this Research, the issues forming the subject matter is: How the PReP Technique can be applied for Germany language reading comprehension for the student of SMA Negeri 12 Surabaya class XI – IPA 2 thema Alltagsleben? the data is the observation of teachers and a students during the PReP Technique method application for Reading comprehension of German language text. The results shows that the process of learning for reading is done using PReP Technique well performing. This is substantiation by the implementation of measures contained in the PReP Technique method application for 5 times the initial Association process, Reflections, Reformation of Knowledge, and Evaluation. By looking at the result of the observation of teachers, enthusiastic student, as well as the results of training given to the students is good enough during the PReP Technique method application. So in this case we will know that the implementation the PReP Technique method application give a positive effect on student’s readiness before reading. Keywords : Pre Reading Plan (PReP) Technique, Reading, German language text